Three-dimensional motion analysis of ten common Asian sitting positions in daily living and factors affect range of hip motions - Phob Ganokroj; Jirayu Chaowalitwong; Pichitpol Kerdsomnuek; Narumol Sudjai; Pisit Lertwanich; Bavornrat Vanadurongwan (BMC Musculoskeletal Disorders, 2021)
Abstract Background Sitting involves many activities of daily life and requires most motion in the hip joint. Asians have more hip flexion and external rotation motions than Westerners owing to cultural and lifestyle differences. Being aware of the normal range of hip motion is essential in clinical practice. Limited research has focused on the hip motions of common sitting positions. The objective was to determine the hip motions of 10 common sitting positions, and to determine whether gender or being overweight affects the range of hip motions. Methods An experimental cross-sectional study was conducted to determine hip motions by using a standard, three-dimensional, motion-analysis system. Healthy subjects performed 10 sitting positions during 3 trials. All hip-kinematic data were measured on the dominant leg of each participant, except for the right- and left-monk positions (both hips were analyzed). Density plots were constructed and statistical analyses were performed to detect the differences between groups (male and female; non-overweight and overweight). Results The 48 participants comprised 24 males and 24 females. Most were right-leg dominant (45 participants, 93.8%). Of the 22 participants in the overweight group (body mass index ≥23 kg/m2), 18 (75%) were male. Squatting showed the highest flexion angle (99.7°, 47.3°–122°). Cross-legged sitting had the highest abduction angle (28.9°, 9.9°–45.7°) and the largest external rotation angle (62°, 37.6°–81.7°). In the female group, there were trends toward a greater flexion angle (4 out of 10 sitting positions) and a smaller abduction angle (6 out of 9 positions), with P values < 0.05. As to body weight, the overweight participants had a smaller flexion angle but a greater abduction angle, with 5 out of 9 positions having a P value < 0.05. Kinematic data of the transverse plane revealed that the heterogeneity of the rotational angles depended on the sitting position. Conclusions This study provided the functional hip motions of common Asian sitting positions. The kinematic data can be utilized in clinical practice as reference values to determine safe positions. Gender and being overweight affected the hip angles in the sagittal and frontal planes. Trial registration Number TCTR20181021004 , retrospectively registered at the Thai Clinical Trials Registry (http//:www.clinicaltrials.in.th).